2020
DOI: 10.32598/jpr.8.2.79
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nasoalveolar Molding on Nasal Symmetry in Patients With Cleft Lip and Palate: A Systematic Review

Abstract: Context: One of the main types of nasal deformity is unilateral cleft lip/palate, which affects the process of breathing and smelling. It is supposed that nasoalveolar molding (NAM) has a positive effect on the reduction of the tension in lips and helps to simplify or even eliminate the subsequent orthodontic treatment. Objective: This systematic review of papers focused on the effectiveness of NAM in patients with unilateral cleft lip/palate. Data Sources: The web search of Google Scholar, PubMed, Web of Scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 50 publications
0
17
0
2
Order By: Relevance
“…The various problems associated with such a defect like compromised physical appearance, speech difficulties, feeding problems, repeated infections, commitment to attend clinical appointments causing absence from school/work and financial burden leads to stigmatization of the problem 15 . A number of studies have quantified the morphological changes brought about by the pre surgical orthopedic procedures carried out prior to the primary lip repair 19,20,21 , but only a few have assessed the parent's perception about the outcome of this procedure. In this study, we found that the mothers could very well appreciate the morphological changes in all the 5 parameters evaluated for facial appearances.…”
Section: Discussionmentioning
confidence: 99%
“…The various problems associated with such a defect like compromised physical appearance, speech difficulties, feeding problems, repeated infections, commitment to attend clinical appointments causing absence from school/work and financial burden leads to stigmatization of the problem 15 . A number of studies have quantified the morphological changes brought about by the pre surgical orthopedic procedures carried out prior to the primary lip repair 19,20,21 , but only a few have assessed the parent's perception about the outcome of this procedure. In this study, we found that the mothers could very well appreciate the morphological changes in all the 5 parameters evaluated for facial appearances.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the tip of the nose points toward the cleft side, whereas the septal base points toward the noncleft side. This process may lead to NSD, especially in the anterior part (Namdar et al, 2020). The septal deviation may cause a narrowed or blocked meatus pushing the middle concha toward the lateral wall.…”
Section: Discussionmentioning
confidence: 99%
“…Cuál es la evidencia Véase matriz de evidencia en Epistemonikos más abajo. Encontramos 14 revisiones sistemáticas (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) que incluyen 39 estudios primario en 57 referencias, de las cuales cinco corresponden a ensayos aleatorizados (31,42,49,57,74) , reportados en 21 referencias (26,27,29,31,(38)(39)(40)42,45,48,49,54,57,(71)(72)(73)(74)(75)(76)(77)(78) (17 referencias pertenecen al hilo de publicación "DUTCHCLEFT") Esta tabla y el resumen en general se basan en estos últimos, dado que los estudios observacionales no aumentaban la certeza de la evidencia existente, ni entregaban información adicional relevante. en parámetros sagitales, verticales y transversales a los cuatro a seis años (baja certeza de evidencia).…”
Section: Acerca Del Conjunto De Evidencia Para Esta Preguntaunclassified